MONITORING FASE PERTUMBUHAN PADI DENGAN SENTINEL-2 DAN PENGARUH FAKTOR FISIK LINGKUNGANNYA - Afifah, Nur; Astuti, Ike Sari (JURNAL GEOGRAFI, 2024)
Rice is a staple food for the majority of Indonesia's population. Therefore, monitoring of rice growth phase and rice phenology is important. Remote sensing technology with Sentinel-2 imagery is applied to quickly obtain data over a large area at PT. Sang Hyang Seri. The NDVI algorithm is used to monitor plant growth and is correlated with plant age to determine the growth phase of rice. The effect of rainfall, soil type and slope were correlated to the NDVI value and the differences in NDVI values were analyzed for the differences in these physical factors. The results showed that the trend of the NDVI value of the rice growth phase was in the form of a parabolic curve of the order-2. The age of rice is generally 110 days old. Land units are divided into 3, according to these physical factors (OATRAL, DFTRL, DFTTL). The factors of rainfall, soil type and slope have an effect on plant fertility, but have no significant effect on the age of rice plants. The duration of the nursery affects the age of rice planting.